ANALISIS YIELD-EFFORT CURVE DAN PRODUKSI SEKTOR PERIKANAN TANGKAP DI KABUPATEN ACEH BESAR - Muhifuddin Muhifuddin; Abd. Jamal; Asmawati Asmawati (Jurnal Ekonomi dan Kebijakan Publik Indonesia, 2018)
AbstractThe purpose of this research to determine thecatching fishery sector clasified in the basic sector ornon basic sector in the structure of economy and to seethe relationship and impact of the fishing effort to theproduction of catching fishery sector in Aceh BesarRegency. This research uses Location Quotion (LQ)and Multiple Regression analysis. From the result ofresearch known that catching fishery sector is basesector in economic structure. The effort fishing and theproduction of catching fishery have a positiverelationship. The number of fishing effort increase 1trip will increase the number of production 0.007 tonwith the assumption that other variables are constant.To increase the production of catching fishery, thegovernment should provide such as fuel subsidy, gillnet, and ship to the fisherman.